Exploring alternative marine lipid sources as substitutes for fish oil in Farmed Sea bass (Dicentrarchus labrax) and their influence on organoleptic, chemical, and nutritional properties during cold storage - Filipa-Silva, Andreia; Marques, Alexandra; Salgado, Maria Antónia; Abreu, Helena; Dias, Jorge; Valente, Luisa M. P. (Frontiers in Sustainable Food Systems, 2023)
This study evaluated the replacement of fish oil (sardine oil) by different combinations of alternative marine lipid ingredients as sources of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in European sea bass (Dicentrarchus labrax) throughout 14 days of ice storage. A practical diet (SARDINE) was used as a control, which included 9% sardine oil and 4.4% soybean oil, providing 2.3% of EPA + DHA. Two other experimental diets were formulated to achieve the same EPA + DHA values but completely devoid of soybean oil. In the ALGABLEND diet, 6.7% of salmon oil (salmon by-product) and 2% of algae biomass (Algaessence Feed™) partially replaced sardine oil. In the ALGAOIL diet, sardine oil was totally replaced with 10.1% salmon by-product oil and 3.3% algae oil (Veramaris®). All diets were equally well-accepted by European sea bass, resulting in similar growth performance, somatic indexes, and whole body composition. At the end of the trial, no significant differences were found in the EPA + DHA levels of fish muscle between dietary treatments, resulting in high values of EPA + DHA (> 0.62 g 100 g−1). Furthermore, replacing fish oil did not significantly affect the organoleptic and chemical properties of the fish samples. Parameters such as pH, water holding capacity, lipid oxidation, antioxidant capacity, color and texture presented similar values to those obtained for fish fed the SARDINE diet during the 14 days of storage in ice. In conclusion, these results show that combining algal oil (Veramaris®), algae blend (Algaessence Feed™) and salmon by-product oil can be a successful strategy for the fortification of European sea bass muscle in EPA and DHA while ensuring fish freshness, nutritional quality, and consumers’ health.